2019
DOI: 10.1186/s12929-019-0586-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphisms, promoter methylation, and mRNA expression profile of maternal and placental P53 and P21 genes in preeclamptic and normotensive pregnant women

Abstract: BackgroundPreeclampsia (PE), as a multisystem disorder, is associated with maternal hypertension and proteinuria. Apoptosis seems to be involved in the pathophysiology of PE, although its precise pathogenic mechanisms are not well established. In this study, we aimed to identify the association between maternal TP53-rs1042522, P21-rs1801270, and P21-rs1059234 polymorphisms and PE. In addition, we examined the effects of promoter methylation and TP53 and P21 polymorphisms on placental mRNA expression in PE wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…In addition, we revealed that p53 was significantly elevated in early-onset PE placentas. This observation confirms other reports of increased p53 in PE and FGR complications ( 43 , 65 , 68 , 69 ). Since p53 is involved in regulating apoptotic processes ( 70 ), increased p53 may lead to increased apoptosis of trophoblast cells ( 43 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we revealed that p53 was significantly elevated in early-onset PE placentas. This observation confirms other reports of increased p53 in PE and FGR complications ( 43 , 65 , 68 , 69 ). Since p53 is involved in regulating apoptotic processes ( 70 ), increased p53 may lead to increased apoptosis of trophoblast cells ( 43 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the down-regulation of p21 is required to induce apoptosis. Similarly, a further in vitro study confirmed that p21 is down-regulated and p53 is up-regulated in trophoblast cells of preeclamptic placentas (68). In contrast to our findings, Cindrova-Davies et al (73) found that p21 was not significantly different between preterm labor and early-onset PE placentas.…”
Section: Discussionsupporting
confidence: 52%
“…It has been shown that the G allele of rs1042522 in p53 comparing with C allele decreases proapoptotic activity and finally mediates the reduction of the p53 pathway in concert with other p53 targets . To our knowledge, there is no published report regarding to the effect of this polymorphism on gene expression and cancer risk, however, we previously examined the role of rs1042522 on p53 mRNA expression in preeclamptic placentas and found no relationship between this polymorphism and p53 mRNA expression . Although these two amino acids have different properties, despite many studies, there is no exact finding on the role of codon 72 polymorphism in cancer development.…”
Section: Introductionmentioning
confidence: 95%
“…14 To our knowledge, there is no published report regarding to the effect of this polymorphism on gene expression and cancer risk, however, we previously examined the role of rs1042522 on p53 mRNA expression in preeclamptic placentas and found no relationship between this polymorphism and p53 mRNA expression. 15 Although these two amino acids have different properties, despite many studies, there is no exact finding on the role of codon 72 polymorphism in cancer development. As Wang et al reported the relationship between TP53 rs1042522 polymorphism and thyroid carcinoma in Caucasians but not in Asians.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in smokers who are also alcoholics, this might contribute to increase susceptibility to the development of carcinoma of the larynx [ 49 ]. Other disruptions in the P53 pathways might result in SNP polymorphisms at the downstream P21, similar to a case in which a P21 polymorphism involving C>A modification at rs1801270 causes the progression of uterine leiomyoma [ 50 ], but decreases the risk of preeclampsia [ 51 ]. Several reports have mentioned that TSU plays an important role in the occurrence of SNP mutations [ 38 , 52 ].…”
Section: Introductionmentioning
confidence: 99%